Efficacy of multicomponent treatment in fibromyalgia syndrome: A meta‐analysis of randomized controlled clinical trials - Häuser, Winfried; Bernardy, Kathrin; Arnold, Bernhard; Offenbächer, Martin; Schiltenwolf, Marcus (Arthritis and rheumatism, 2009)
Objective To systematically review the efficacy of multicomponent treatment of fibromyalgia syndrome (FMS). Methods We screened Medline, PsychINFO, Scopus, and the Cochrane Library (through December 2007), as well as reference sections of original studies, reviews, and evidence‐based guidelines. Randomized controlled trials (RCTs) on the multicomponent treatment (at least 1 educational or other psychological therapy with at least 1 exercise therapy) of FMS were analyzed. Results We included 9 (of 14) RCTs with 1,119 subjects (median treatment time 24 hours) in the meta‐analysis. Effects were summarized using standardized mean differences (SMDs) or weighted mean differences (WMDs). There was strong evidence that multicomponent treatment reduces pain (SMD −0.37; 95% confidence interval [95% CI] −0.62, −0.13), fatigue (WMD −0.85; 95% CI −1.50, −0.20), depressive symptoms (SMD −0.67; 95% CI −1.08, −0.26), and limitations to health‐related quality of life (HRQOL) (SMD −0.59; 95% CI −0.90, −0.27) and improves self‐efficacy pain (SMD 0.54; 95% CI 0.26, 0.82) and physical fitness (SMD 0.30; 95% CI 0.02, 0.57) at posttreatment. There was no evidence of its efficacy on pain, fatigue, sleep disturbances, depressive symptoms, HRQOL, or self‐efficacy pain in the long term. There was strong evidence that positive effects on physical fitness (SMD 0.30; 95% CI 0.09, 0.51) can be maintained in the long term (median followup 7 months). Conclusions There is strong evidence that multicomponent treatment has beneficial short‐term effects on the key symptoms of FMS. Strategies to maintain the benefits of multicomponent treatment in the long term need to be developed.